Hukum Istibdal Harta Benda Wakaf Menurut Ulama Syafi’iyyah Dan Ulama Hanafiyyah (Studi Kasus Istibdal Harta Benda Wakaf Masjid Menjadi Rumah Potong Hewan Qurban Di Desa Teluk Bakung) - Shafiatul Muna (Journal Smart Law, 2023)
The aim of the research is to understand the Istibdal law for waqf property from mosques to become sacrificial slaughterhouses in Teluk Bakung Village according to the opinion of Syafi'iyah and Hanafiyah. The method used is qualitative research with a liberal research approach. Researchers conducted literature searches through various sources such as scientific journals, books, articles and other related publications. The research results show that Imam Al-Nawawi (Shafi'iyyah School) prohibits the sale or replacement of waqf assets, namely Istibdal. He is of the opinion that waqf assets should be allowed to be used until they are completely used up. Imam Al-Sarkhasi (Hanafiyyah School) allows the Istibdal of waqf assets to spend the waqf by borrowing. This policy focuses on the maslahah aspects that accompany this practice. According to Hanafiah, istibdal can be done by anyone, whether the waqif himself, other people or judges. This permission is without choosing the type of property donated, whether it is land that is inhabited (managed), unoccupied (not managed), movable (manqul), immovable (iqar). There are differences of opinion between the two Imams above. In the opinion of Imam Al-Sarkhasi, istibdal of waqf assets is permissible if maslahah occurs and is permissible conditionally. Imam AlNawawi's opinion also does not justify istibdal because he understands the text of the hadith that waqf property cannot be bought and sold, inherited and exchanged. Istibdal waqf mosque property becomes a slaughterhouse among followers of the Shafi'iyyah school of thought is not permitted